Existentialism on Social Media: The ‘Look’ of the ‘Crowd’ - Cheong, Marc (Journal of Human-Technology Relations, 2023)
Social media has become a basis for helping us maintain human contact, especially as our alienation from our phenomenological experiences of ‘being human’ is becoming apparent due to the pandemic. I argue for how existentialist philosophy is crucial, more than ever, to interrogate our social media usage, which is a ‘necessary evil’ in our daily lives. Firstly, Kierkegaard’s critiques of the crowd and of the press are equally applicable to social media, which plays both roles: enabling an anonymous mass of public opinion and doubling-up as an information source, reducing responsibility on the individual. Secondly, social media leads to an intrinsic pressure to objectify one's self (as portrayed) due to the possibility of an omnipresent Other, based on the technological design of networks. I will link my arguments on social media to other existential ideals and will conclude by suggesting changes that may promote existential ideals in one’s social media portrayal and engagement.